Bioproductive Parameters and Fatty Acids Profile of the Meat from Broilers Treated With Flax Meal and Grape Seeds Meal - Margareta Olteanu; Rodica Diana Criste; Tatiana Dumitra Panaite; Mariana Ropota; Petru Alexandru Vlaicu; Raluca Paula Turcu (Scientific Papers Animal Science and Biotechnologies, 2023)
The 3-week feeding trial was conducted on 120, Cobb 500 chicks (14 days) assigned to two groups (C, E). Compared to C diet formulation (corn, wheat, soybean meal and flax meal as basic ingredients), E diet formulation also included 3% grape seeds meal as natural antioxidant. The feed intake and the gains were not significantly (P>0.05) different between groups. Six broilers/group were slaughtered in the end of the trial and 6 samples of breast and thigh meat/group were formed and assayed for the feeding value. The proportion of polyunsaturated fatty acids (PUFA) was significantly (P≤0.05) higher in group E than in group C, both for the chicken breast: 32.6±0.87g (E) vs 29.29±0.96 g/100 g total fatty acids (C), and in the thigh: 37.68±2.07g (E) vs 29.58±1.16 g/100g total fatty acids (C). The content of alfa linolenic acid (ALA) was significantly (P≤0.05) higher also in group E, both in the breast meat: 0.99±0.02g (E) vs 0.89±0.34g/100g total fatty acids (C), and in the thigh meat: 1.20±0.07g (E) vs 0.90±0.0g/100g total fatty acids (C). The omega-3 PUFA content was the highest in the breast meat sample, 2.19±0.07g/100g total fatty acids (E), with no significant (P>0.05) differences between groups.